2022
DOI: 10.3389/fimmu.2022.827146
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Spike Protein 1 Activates Microvascular Endothelial Cells and Complement System Leading to Platelet Aggregation

Abstract: Microvascular thrombosis is associated with multiorgan failure and mortality in coronavirus disease 2019 (COVID-19). Although thrombotic complications may be ascribed to the ability of SARS-CoV-2 to infect and replicate in endothelial cells, it has been poorly investigated whether, in the complexity of viral infection in the human host, specific viral elements alone can induce endothelial damage. Detection of circulating spike protein in the sera of severe COVID-19 patients was evaluated by ELISA. In vitro exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 99 publications
2
65
1
Order By: Relevance
“… Kovacs-Kasa [ 69 ], 2022 Experimental cell HLMVEC Endothelial permeability measurement of HLMVEC exposed to plasma from SARS-CoV-2 patients ECIS C3aR and C5aR antagonists Non-severe, severe SARS-CoV-2 induced permeability is not affected by C3a or C5a inhibitors. Perico [ 68 ], 2022 Experimental HMEC-1 Endothelial cells exposed to SARS-CoV-2 derived spike protein 1 Immunofluorescence C3aR and C5aR antagonists Severe Endothelial dysfunction induced by SARS-CoV-2-derived S1 protein triggers exuberant complement deposition on activated microvascular endothelial cells C3a and, to a lesser extent, C5a, further amplify complement activation that fuels inflammation in response to S1. Zhang [ 66 ], 2021 Experimental cell Neutrophils and HUVECs Neutrophils exposed to plasma from HCs or COVID-19 patients and HUVECs exposed to supernatant of neutrophils cultured with COVID-19 plasma MPO-DNA, cell viability assay Anti-C3a and anti-C5a antibodies Mild or severe Anaphylatoxins C3a and C5a in the plasma of COVID-19 patients strongly induced NET formation, which could be relieved by CPB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Kovacs-Kasa [ 69 ], 2022 Experimental cell HLMVEC Endothelial permeability measurement of HLMVEC exposed to plasma from SARS-CoV-2 patients ECIS C3aR and C5aR antagonists Non-severe, severe SARS-CoV-2 induced permeability is not affected by C3a or C5a inhibitors. Perico [ 68 ], 2022 Experimental HMEC-1 Endothelial cells exposed to SARS-CoV-2 derived spike protein 1 Immunofluorescence C3aR and C5aR antagonists Severe Endothelial dysfunction induced by SARS-CoV-2-derived S1 protein triggers exuberant complement deposition on activated microvascular endothelial cells C3a and, to a lesser extent, C5a, further amplify complement activation that fuels inflammation in response to S1. Zhang [ 66 ], 2021 Experimental cell Neutrophils and HUVECs Neutrophils exposed to plasma from HCs or COVID-19 patients and HUVECs exposed to supernatant of neutrophils cultured with COVID-19 plasma MPO-DNA, cell viability assay Anti-C3a and anti-C5a antibodies Mild or severe Anaphylatoxins C3a and C5a in the plasma of COVID-19 patients strongly induced NET formation, which could be relieved by CPB.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of C3aR (SB 290157) and C5aR (mix of W-54011 and DF2593) in human airway epithelial cells led to mitigation of viral infection and a decrease of the inflammatory response in airways, whereas inhibition of C5aR also maintained the epithelial integrity of human airway epithelia infected with SARS-CoV-2 [ 64 ]. One experimental study in human microvascular endothelial cells (HMEC-1) showed that endothelial dysfunction induced by SARS-CoV-2 derived S1 protein triggered complement deposition on activated microvascular endothelial cells [ 68 ]. In particular C5a further amplified activation of the complement system, which contributed to inflammation in response to S1 [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of C3a and C5a further amplifies S1-induced complement activation. This eventually leads to increased platelet aggregation on the endothelial cells of microvessels [ 30 ]. Platelets, in addition to their conventional involvement in thrombosis and hemostasis, also play important roles in inflammatory and immunological processes [ 31 33 ], which indirectly influence immune responses by the release of antimicrobial peptides and cytokines and directly amplify immune responses by interacting with lymphocytes, monocytes, and neutrophils once pathogens have been detected [ 34 ].…”
Section: Discussionmentioning
confidence: 99%